Writing for conferences a handbook for graduate students and faculty - Mallete, Leo (Greenwood, 2011)
Writing for Conferences: A Handbook for Graduate Students and Faculty serves as an essential guide for graduate students who want to publish the results of the research projects of their graduate program to maximum effect. It explains the conference publication process step-by-step and answers all of the questions asked by students inexperienced in publishing. The book is also a valuable reference manual for previously published authors, providing insightful sections on ethics in publishing, dress and grooming, presentation tips, and networking techniques to develop further research and career opportunities.